Performance of Shell Peeling Machine for Koro Pedang (Canavalia ensiformis) - Agus Sutejo; Gilang Ramdani; Rafi Rizky Mulyadi; Dinur Saptiadi (The University of Lampung, 2026)
The increasing demand for tempeh made from koro pedang (Canavalia ensiformis) beans requires large quantities of kernels processed rapidly and efficiently. This study evaluated the performance of a newly developed outer-shell peeling machine to enhance peeling capacity and seed–shell separation efficiency. Experiments were conducted at three rotational speeds (730, 820, and 960 rpm) with three replications per treatment. Observed parameters included peeling capacity, peeling efficiency, separation efficiency, percentage of broken seeds, and fuel consumption. Results showed that increasing rotational speed improved peeling capacity from 32.41 to 51.77 kg/h, with the highest value obtained at 960 rpm. Maximum peeling efficiency reached 93.09%, while the highest separation efficiency was approximately 83.09% at 960 rpm. The percentage of broken seeds remained low (≤0.99%). Fuel consumption was 0.43 L/h, indicating good energy efficiency for small- to medium-scale operations. Overall, the machine use increases production throughput, shortens processing time, and reduces reliance on manual labour, supporting the sustainable development of tempeh industries based on koro pedang beans.